Testing Reactivity Descriptors for the Electrocatalytic Activity of Opg Hybrid Electrodes Modified with Iron Macrocyclic Complexes and Mwcnts for the Oxidation of Reduced Glutathione in Basic Medium - Zagal-Moya, J; Zagal-Moya, J; Ponce-Hormazabal, I; Gutierrez-Ceron, C; Gutierrez-Ceron, C (Pleiades Publishing, 2019)
Abstract: In this work we have tested the Fe(III)/(II) redox potential of the catalysts as a reactivity descriptors of iron macrocyclic complexes (FeN4) adsorbed on multi-walled carbon nanotubes (MWCNTs) and deposited on ordinary pyrolytic graphite (OPG). The reaction examined is the oxidation of glutathione (GSH) a biologically important molecule. The experiments were conducted in 0.1 M NaOH and kinetic measurements were performed on MWCNT previously modified with FeN4 macrocycle complexes. This modified FeN4–MWCNTs were deposited on pristine OPG electrodes. From previous work it is known that for FeN4 complexes directly adsorbed on OPG, the activity as (log i)E plotted versus the Fe(II)/(I) redox potential follows a volcano correlation for the oxidation of glutathione. We wanted to test these correlations on hybrid electrodes containing MWCNTs and essentially the carbon nanotubes have no influence in these correlations and the redox potentials a are good reactivity descriptors, regardless of the way the FeN4 catalysts are attached to the electrode. Further, we find volcano correlations when using the Fe(II)/(I) and the Fe(III)/(II) redox potentials as reactivity descriptors. The volcano correlation when using the Fe(III)/(II) redox potential exhibits a maximum at E° = –0.26 V vs SCE which is close to the potential for comparing the different activities. This interesting result seems to indicate that the maximum cannot be explained only in terms of the Sabatier principle where θRS, the surface coverage of adsorbed intermediate is close to 0.5 but instead to a surface coverage of active sites θFe(II) equal to 0.5, which occurs at the Fe(III)/(II) formal potential. © 2019, Pleiades Publishing, Ltd.